FACTORS AFFECTING SUCCESS OR FAILURE IN SOFTWARE PROJECTS IN THE KINGDOM OF SAUDI ARABIA (CAHIERS MAGELLANES-NS, 2024)
This study aimed to identify factors affecting the success or failure of software projects in the Kingdom of Saudi Arabia. The study used the descriptive method as a study approach and employed the questionnaire as a study tool. The study included (111) employees in some software projects in administrative, medical, educational, military and commercial facilities of the public and private sectors in the Kingdom of Saudi Arabia. The study findings indicated that administrative projects were the most common type of project, with government projects having a higher percentage. Teams with one to ten members were the most typical size, and most projects were completed within six months to a year. Project success depended on an appropriate timeline, teamwork, and thorough task schedules. Project failures were often caused by delays, lack of teamwork, and legal permission requirements. Public opinion on project success was not significantly impacted by project type or team size. The study recommended the need to analyze and estimate the project, identify potential risks, conduct training for team members, develop a clear task schedule, and focus on selecting team members to achieve project objectives and ensure adaptability and collaboration.